Analysing news coverage on homosexuality in Malay language newspapers in Malaysia, 1998-2012 - Syamsul Zahri Subir, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Homosexuality is a complex issue in Malaysia, owing to its identity as a conservative nation with a Malay-Muslim majority. Here, homosexuality is not only unrecognised but also negatively viewed by society. Unsurprisingly, the homosexuality issue is not widely covered in the news media in Malaysia. However, changes in local political climate and communication technology require researchers to evaluate the current literature. Furthermore, the number of researches, particularly homosexuality coverage in the Malaysian media remains insignificant. This study attempts to draw a deeper understanding of how newspapers in Malaysia are utilised in constructing homosexuality coverage by employing a modified version of Huckin’s study (2002) of qualitative content analysis. A random sample of 463 homosexuality coverage was collected from two Malay language newspapers, Utusan Malaysia and Berita Harian spanned from 1998 to 2012. The findings revealed that homosexuality coverage are largely social-cultural-political themes intertwined, supported by official government and religious sources with the coverage mostly not geared towards the progressive content, politically motivated and dominantly narrated in Islamic widespread pitch. This study argues that homosexuality coverage was constructed in such a way to serve the interest of dominant Malay political hegemony while the normative definition of sexuality remains to be heteronormative patriarch from the long history of the patriarchal institution. This study concludes by challenging the media as a ‘cultural resource’ that ‘inherently’ homophobic. The study suggests that media should work in ubiquitous and consider redefining the role, particularly in 21st-century democratic Malaysian nations.